PENENTUAN LOKASI TITIK BOR AIR TANAH BERDASARKAN METODE TAHANAN JENIS 2D DI DESA SUBUR MAKMUR KABUPATEN KOTABARU, KALIMANTAN SELATAN - Rudy Hendrawan Noor; Ishaq Ishaq (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2021)
Subur Makmur Village is an area where the availability of clean water is difficult, especially during the dry season. One of the sources of water that can be used by the villagers is groundwater. However, to obtain groundwater, it is necessary to drill wells and investigate the aquifer layer first. This study aims to obtain an overview of the subsurface layers based on the resistivity properties of the rock, so that the aquifer layer can be identified and can determine the exact location of the drill point in the prospective aquifer position that may be encountered. The geoelectric method is the most efficient method for detecting aquifer layers. It uses two types of configurations, namely, the Wenner and Wenner-Schlumberger configurations where the number of geoelectric paths is one path. The length of the track used is 540 meters, the number of electrodes is 28 with the spacing between the electrodes is 20 meters. The resistivity cross section for both configurations, obtained resistivity values of 11 - 140 Ohm meters. Composed of 2 (two) rock units, namely graywacke sandstone rock units. Consists of graywacke sandstones with claystone inserts. Density value ≥ 40 Ohm meter. Hydraulic properties, small porosity, small permeability, the potential for groundwater in this unit is small. The position of this unit is at a depth of 40 m. In the cross section, the resistivity is yellow - red. The second rock unit comprising this trajectory is the alteration claystone unit consisting of claystone containing bolders of sandstone / igneous rock. Resistivity value ≤ 40 Ohm meter. The position of this unit is on the Surface to a depth of 40 m. Hydraulic properties, large porosity with very small permeability, the potential for groundwater is very small. In the cross section of this unit resistivity are colored dark blue, blue and green. From the resistivity cross section, it can be determined the position of the borehole which is effectively located in the length range of the trajectory between 360 - 420 meters. Keywords: subur makmur, groundwater, wenner,  wenner-schlumberger